The Role of Members of the Regency/City People's Representative Council (DPRK) Appointment Mechanism as Cultural Representatives in Monitoring Special Autonomy Policies - Lily Bauw (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
This study aims to further examine the role of DPRK members of the appointment mechanism in accommodating the rights of Indigenous Papuans in regional policies to optimize the implementation of Law Number 2 of 2021. The approach used in writing uses a qualitative descriptive approach that aims to describe the role of DPRK members of the appointment mechanism in accommodating the rights of Indigenous Papuans in Keerom Regency policies to optimize the implementation of Law Number 2 of 2021, so as to produce recommendations in the form of ideas to optimize the role of the DPRK. Therefore, this writing uses a literature study approach related to data collection procedures, in the form of scientific sources such as journals, monographs, and reference books. The results of this study reveal that the role of DPRK members of the appointment mechanism as a cultural representation in overseeing the Special Autonomy policy is carried out through strengthening the position of the DPRK appointment mechanism, namely by providing space for the existence of deputy DPRK leaders who come from DPRK members of the appointment mechanism and the existence of special groups. The existence of deputy leaders and special groups makes the bargaining position of the DPRK appointment mechanism strong in fighting for the rights of Indigenous Papuans so that they can become part of regional policies.